Hedgehog signaling pathway and its targets for treatment in basal cell carcinoma - Cucchi, Danilo (J Exp Pharmacol, 2012)
Basal cell carcinoma (BCC) of the skin is the most common type of cancer and accounts for up to 40% of all cancers in the US, with a growing incidence rate over recent decades in all developed countries. Surgery is curative for most patients, although it leaves unaesthetic scars, but those that develop locally advanced or metastatic BCC require different therapeutic approaches. Furthermore, patients with BCC present a high risk of developing additional tumors. The increasing economic burden and the morbidity of BCC render primary interest in the development of targeted treatments for this disease. Among the molecular signals involved in the development of BCC, the critical role of the morphogenetic Hedgehog (Hh) pathway has become evident. This pathway is found altered and activated in almost all BCCs, both sporadic and inherited. Given the centrality of the Hh pathway in the pathophysiology of BCC, the primary efforts to identify molecular targets for the topical or systemic treatment of this cancer have focused on the Hh components. Several Hh inhibitors have been so far identified – from the first identified natural cyclopamine to the recently Food and Drug Administration-approved synthetic vismodegib – most of which target the Hh receptor Smoothened (either its function or its translocation to the primary cilium). Other molecules await further characterization (bisamide compounds), while drugs currently approved for other diseases such as itraconazole (an antimicotic agent) and vitamin D3 have been tested on BCC with encouraging results. The outcomes of the numerous ongoing clinical trials are expected to expand the field in the very near future. Further research is needed to obtain drugs targeting downstream components of the Hh pathway (eg, Gli) or to exploit combinatorial therapies (eg, with phosphatidylinositol 3-kinase inhibitors or retinoids) in order to overcome potential drug resistance.